2018
DOI: 10.1007/s40195-018-0782-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of La on Microstructure and Corrosion Behavior of AlSi5Cu1Mg Alloy

Abstract: The microstructures and corrosion behavior of AlSi5Cu1Mg alloy modified with different contents of La were investigated. Optical microscopy observations showed that the microstructures of AlSi5Cu1Mg-xLa (x = 0, 0.3, 0.6, and 0.9 wt%) alloy transformed from coarse cellular to fine cellular as the content of La increased from 0 to 0.9 wt%. The results of electrochemical measurement and immersion test in 3.5 wt% NaCl solution showed that the corrosion resistance of AlSi5Cu1Mg-xLa alloy strongly depended on its mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The corrosion resistance of an AlSi5Cu1Mg alloy with different La additions (0.3%, 0.6%, and 0.9%) was examined [12]. It was highlighted that the optimal La addition was 0.6 % reducing the corrosion rate by 40% (from 54 to 22 µAcm 2 ) with respect to the La-free alloy as showed in Table S3.…”
Section: Influence Of Addition Of Rare Earths On Corrosion Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The corrosion resistance of an AlSi5Cu1Mg alloy with different La additions (0.3%, 0.6%, and 0.9%) was examined [12]. It was highlighted that the optimal La addition was 0.6 % reducing the corrosion rate by 40% (from 54 to 22 µAcm 2 ) with respect to the La-free alloy as showed in Table S3.…”
Section: Influence Of Addition Of Rare Earths On Corrosion Resistancementioning
confidence: 99%
“…The effect of the corrosion resistance of Er and Zr on an A-356 alloy obtained by permanent metal mold was studied by Colombo et al [13]. By performing immersion corrosion tests, they observed that the addition of Er decreased the corrosion rate from 45.8 µg/cm 2 d to 4.2 µg/cm 2 d and they associated this improvement with the modification of the morphology of eutectic silicon from The corrosion resistance of an AlSi5Cu1Mg alloy with different La additions (0.3%, 0.6%, and 0.9%) was examined [12]. It was highlighted that the optimal La addition was 0.6 % reducing the corrosion rate by 40% (from 54 to 22 µAcm 2 ) with respect to the La-free alloy as showed in Table S3.…”
Section: Influence Of Addition Of Rare Earths On Corrosion Resistancementioning
confidence: 99%
“…Yang et al [4] reported that the addition of Be to the A357 alloy improved the microstructure of the β-Al 5 FeSi and Si phases, which increased the corrosion resistance of the alloy. Yu et al [5] reported that the addition of rare earth La refined the microstructure of the AlSi5Cu1Mg alloy, which improved the corrosion resistance in 3.5 wt% NaCl solution.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work [13] showed that the addition of 0.6 wt% (Pr+CePr+Ce) had the best refinement effect on the microstructure of AlSi5Cu1Mg alloy. The corrosion resistance of the alloy depends on the morphology of the microstructure [5,14]. In this paper, our aim is to investigate the effect of (Pr+Ce) addition and T6 heat treatment on microhardness and corrosion of AlSi5Cu1Mg alloy.…”
Section: Introductionmentioning
confidence: 99%
“…The sole addition of Bi is reported to be favorable in obtaining the modified eutectic phase [10]; nevertheless, the addition of Bi along with Sr exhibited the poisoning effect and reduced the modification effectiveness to some extent [11]. Moreover, some other studies [12][13][14][15] claimed that the inclusion of La significantly modifies the microstructure, mechanical, and corrosion resistance properties of Al-Si alloys. Ahmad R [16] investigated the modification role Ce addition; whereas, Jiang et al [17] evaluated the collective effect of rare earth (La and Ce) elements and declared that a suitable amount of rare earth mixture alters almost all microstructure features and improves mechanical properties considerably.…”
Section: Introductionmentioning
confidence: 99%